Deception & manipulation: Argyrodinae spiders as parasites and hosts - Deutsch, Ella K. (2022)
Spiders (order Araneae) are a diverse and successful taxon, present across the world in even extreme environmental conditions. Much of this success is due to their production of silk which, among other uses, forms webs with which to effectively capture prey and avoid predators. However, these resource-intensive external structures are vulnerable to exploitation by organisms utilising the silk structures and captured prey for their own benefit, termed kleptoparasites.